2013
DOI: 10.2478/bvip-2013-0081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fowl adenovirus on replication of vaccine strain of Marek’s disease virus in chickens

Abstract: The aim of the study was to determine the effect of field strain, serotype 7 (FAdV-7 JN-5/10), of fowl adenovirus infection on the replication of Rispens/CVI988 strain of Marek's disease virus. Ninety one-day-old SPF chickens were divided into six groups. The chickens from group I were vaccinated against Marek's disease (MD) and 24 h later infected with the adenovirus; chickens from group II were vaccinated and infected simultaneously; chickens from group III were infected with the adenovirus and 24 h after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The difference in the time of onset could be due to concurrent infection with CAV. Chicken anemia virus may have influenced the course of the disease as a contributing pathogen, affecting the immune response ( Markowski-Grimsrud and Schat, 2003 ), or via secondary effects due to anemia ( Toro et al., 2000 , Niczyporuk et al., 2013 ). The additive effect of CAV with FAdV-4 has been investigated, and their synergism was implicated in severe disease ( Toro et al., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the time of onset could be due to concurrent infection with CAV. Chicken anemia virus may have influenced the course of the disease as a contributing pathogen, affecting the immune response ( Markowski-Grimsrud and Schat, 2003 ), or via secondary effects due to anemia ( Toro et al., 2000 , Niczyporuk et al., 2013 ). The additive effect of CAV with FAdV-4 has been investigated, and their synergism was implicated in severe disease ( Toro et al., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although implicated, the pathogenicity of most AAV, particularly FAdVs, is not well defined ( Niczyporuk et al., 2012 ). Some strains may act as primary or secondary pathogens ( Toro et al., 2000 , Niczyporuk et al., 2012 , Niczyporuk et al., 2013 ). However, under certain conditions, such as inclusion body hepatitis ( IBH ) and hydropericardium hepatitis syndrome ( HPS ), FAdVs have been directly involved, wherein disease has been replicated using field isolates ( Okuda et al., 2006 , Mase et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particular serotypes of FAdV are responsible for a number of different clinical signs, including; inclusion body hepatitis (IBH) gizzard erosion and ulceration (GEU) and hydropericardium hepatitis syndrome (HHS) (Fitzgerald, 2013). Moreover, fowl aviadenoviruses may induce immunodeficiency or influence the failure of chicken vaccinations (Saifuddin &Wilks, 1992 andNiczyporuk et al, 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressors such as IBDV, chicken infectious anemia virus (CIAV), and Marek's disease virus (MDV) are factors that facilitate IBH outbreaks propagation or worsen clinical manifestations of FAdV infections (Morshed, Hosseini, Langeroudi, Fard, & Charkhkar, 2017;Niczyporuk, Woźniakowski, Samorek-Salamonowicz, & Czekaj, 2013). However, several studies showed that IBH might occur as a primary disease (Gomis et al, 2006;Ojkic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%